Plainchant and liturgy in the diocese of Münster in Westphalia : the fifteenth-century Freckenhorst antiphoner (D-MÜd PfA 53) - Brink, Danette (College of Music, 2014)
Includes abstract.|Includes bibliographical references (p. 213-222).